2022
DOI: 10.1039/d2sc02648a
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoconvergent synthesis of anti-1,2-amino alcohols with N-containing quaternary stereocenters via selenium-catalyzed intermolecular C–H amination

Abstract: We report a diastereoconvergent synthesis of anti-1,2-amino alcohols bearing N-containing quaternary stereocenters using an intermolecular direct C-H amination of homoallylic alcohol derivatives catalyzed by a phosphine selenide. Destruction of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…However, we found that the addition of lithium acetate greatly improved the desired reactivity, allowing us to obtain 68% of the allylic amide product. In our previous work, basic additives have been shown to improve the yield, presumably to scavenge acidic byproducts of the reaction . To test the generality of this protocol, we screened a few natural terpene scaffolds using trifluoroacetamide as the nitrogen source and obtained moderate to good yields of the desired amination products in every case (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, we found that the addition of lithium acetate greatly improved the desired reactivity, allowing us to obtain 68% of the allylic amide product. In our previous work, basic additives have been shown to improve the yield, presumably to scavenge acidic byproducts of the reaction . To test the generality of this protocol, we screened a few natural terpene scaffolds using trifluoroacetamide as the nitrogen source and obtained moderate to good yields of the desired amination products in every case (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, basic additives have been shown to improve the yield, presumably to scavenge acidic byproducts of the reaction. 10 To test the generality of this protocol, we screened a few natural terpene scaffolds using trifluoroacetamide as the nitrogen source and obtained moderate to good yields of the desired amination products in every case (Scheme 3). Other amides were not suitable coupling partners under these conditions, presumably due to competing Hofmann rearrangement (see the Supporting Information (SI) for examples).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Several methods have been developed to synthesize allylamines that involve forming the C-N bond by substitution on allylic systems, either through simple SN2 reactions 7 or through many recent and elegant approaches to allylic C-H amination. [8][9][10][11] However, these methods require the pre-synthesis of the allyl fragment, which means the majority of these methods give rise to disubstituted or 1,1-symmetrical trisubstituted alkene products due to the challenge of accessing more complex allyl substrates (Scheme 1a).Meanwhile, methods that make use of the amine as a structural feature to facilitate further elaboration have generally been limited to protected amine substrates. [12][13][14] We were particularly interested in how the use of C-H activation could enable rapid access to substitution of the alkene from simple precursors, rather than relying on low-yielding and multistep reaction sequences to prepare unsymmetrical 3,3-disubstituted allylamines.…”
mentioning
confidence: 99%